2020
DOI: 10.1101/2020.01.16.908939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early life stress causes persistent impacts on the microbiome of Atlantic salmon

Abstract: 1

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…Our finding that corticosteroid treatments affect gut microbiome diversity and composition is consistent with studies in other organisms. Previous studies showed that cortisol elevation due to acute stressors associates with altered diversity and composition of the gut and skin microbiome in Atlantic salmon (Salmo salar) 16,18 . Specific environmental stressors, including thermal stress 55,56 and crowding stress 57 modulate the microbiota of other fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that corticosteroid treatments affect gut microbiome diversity and composition is consistent with studies in other organisms. Previous studies showed that cortisol elevation due to acute stressors associates with altered diversity and composition of the gut and skin microbiome in Atlantic salmon (Salmo salar) 16,18 . Specific environmental stressors, including thermal stress 55,56 and crowding stress 57 modulate the microbiota of other fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research on the gut microbiome of freshwater Atlantic salmon suggests that even when alpha diversity is not altered, difference may be present in the beta diversity, for example, Chao1 richness and Shannon diversity were not altered by acute cold stress or a chronic environmental stress but the beta diversity was altered 57 . In early stage salmonids when the dietary protein composition is altered, existing studies observed a signi cant shift in the beta diversity and composition of the gut microbiome, in Atlantic salmon (Salmo salar) 58 , in Rainbow trout (Oncorhynchus mykiss) 35,59 , and in Arctic charr (Salvelinus alpinus) 60 .…”
Section: Discussionmentioning
confidence: 99%
“…and Aeromonas sp, were also particularly abundant in fish that had high levels of faecal cortisol. These genera include a range of opportunistic fish pathogens (Austin & Austin 2007), and tend to increase following exposure to different types of environmental stress in fish (Boutin et al 2013; Uren Webster et al 2019), suggesting they may represent a common signature of stress exposure. In mammals, experimental administration of cortisol results in a similar reduction in probiotic lactic acid-producing bacteria and an increase in pro-inflammatory microbiota (Huang et al 2015; Petrosus et al 2018; Wu et al 2018), suggesting that these bacteria taxa could represent useful biomarkers of stress across vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the microbiome is likely to represent an important mechanism by which stress affects fish health, welfare and performance in aquaculture. There is some evidence that environmental and social stressors disrupt microbial communities associated with the fish gut and skin (Boutin et al 2013; Sylvain et al 2016; Uren Webster et al 2019; Zha et al 2018), however, a potential role of cortisol in mediating these effects is unknown. We hypothesised that stress-induced cortisol production would directly disrupt the fish microbiome.…”
Section: Introductionmentioning
confidence: 99%